How Does Fintech Development Affect Financing Constraints of Smes? Evidence From China - Yang Jian; Zhang Yawen; Gong Jinguo; Liu Tong (ECONOMICS)
Small and medium-sized enterprises (SMEs) play an indispensable role in China’s economy through making huge contributions to GDP, national employment, financial innovation and government taxation. However, SMEs in China have long faced financing constraints due to their inherent problems, such as financial information asymmetry, immature governance mechanisms, and lack of collateral under the traditional financial system, which have hindered their long-term development. In recent years, financial technology (Fintech) has entered a rapid development track, especially in China, providing new ideas and methods for solving the financing difficulties of SMEs from a technical perspective. In order to examine this, this paper measures the degree of financing constraints through the cash flow sensitivity of cash model and explores how the Fintech development affects financing constraints of SMEs in China and how this impact further communicated to the performance and the risks of SMEs by adopting two-way fixed effects models. The results show that Fintech could alleviate the financing constraints of SMEs. Furthermore, the mediating role of ownership is identified, presenting a better mitigating effect of Fintech on the financing constraints for private SMEs. In addition, both the performance and the risks of SMEs showed the upward single-sided U-shaped relationship with the increase of the Fintech development index, which indicates that Fintech could amplify performance while magnifying the risks of SMEs. The findings of this paper offer an important implication for China that regulatory authorities should consider and balance the financing constraint mitigation effect and risk amplification effect of Fintech.